Processing of zirconia and calcium aluminate cement mixtures by spark plasma sintering - Bruni, Yesica Lorena (2015)
Spark Plasma sintering (SPS) was applied for the densification of Calcia stabilized ZrO2 based composites obtained frommixtures of pure zirconia (m-ZrO2) and calcium aluminate cement (HAC). Two commercial powders of pure zirconia wereemployed as reactants. One of these powders had a coarse mean particle size (d50 = 8 μm) and the other was a submicrometersized power (d50 = 0.44 μm). Several compositions containing different proportions of HAC (5 to 30 mol. % CaO in ZrO2)were sintered by SPS at temperatures between 1200 and 1400ºC under a pressure of 100 MPa during 10 min. The effect ofprocessing conditions on phase composition, densification, microstructure and Vickers hardness of the obtained compositeswas examined. SPS significantly enhanced the densification in both type of composites (relative density > 93 %) as comparedto those previously produced by conventional sintering. Composites with low CaO content consisted of mixtures of c-ZrO2,(Ca0.15Zr0.85O1.85), unreacted m-ZrO2 and calcium dialuminate (CaAl4O7 or CA2). The highest hardness was determined forcomposites sintered at 1400ºC being related to the maximum relative density (~ 99 %). High densification of compositeswith 30 mol. % CaO composed by similar proportions of CaAl4O7 and c-ZrO2 were obtained even at 1200ºC but led to aslightly lower hardness. In general, the use of the finer m-ZrO2 powder contributed to increase both the c-ZrO2 content anddensification of composite sintered at a relatively lower temperature. For these composites, best hardness (Hv near to 10GPa) resulted when the microstructure consisted of a fine grained ZrO2 matrix surrounding the dispersed CaAl4O7 grainsinstead of large interconnection between grains of both phases existed.